Mortality Risk for Mental Health Related Frequent Attenders at Accident and Emergency Departments. (20th October 2021) - Saunders, P; Rahim, S
Abstract: Background: Individuals with a psychiatric history present more often to an emergency setting than other patients leading to higher costs, resource utilisation and potentially longer waiting times. Frequent attenders are more likely to commit suicide sooner after their last attendance than other attenders. Methods: Retrospective cohort study of 20, 493 patients attending emergency services 01 November 2013-31 October 2017 including mortality within six months of last attendance using the four most common definitions of frequent attender. Results: The most frequently used definitions identified were ≥ four, five, three, and six attendances in 12 months. Mean age ranged from 37 to 41 years depending on the definition used. Males were at a significantly higher risk of early mortality (RR 1.81, p < 0.0001 to 1.84, p < 0.0001). Relative risk of mortality associated with higher frequency of attendance definition increased from 3.68 (p < 0.0001) to 8.47 (p < 0.0001). Risk of mortality increased with age for all definitions. Ethnicity showed no statistical significance for any definition contrary to the literature. Conclusions: Frequent attenders, irrespective of definition, were at significantly higher risk of early mortality. That risk more than doubled depending on the definition. It is recommended that ≥ 4 attendances in a year be adopted as a consensus definition. Key messages: Frequent attenders, irrespective of definition, were at significantly higher risk of early mortality. That risk more than doubled depending on the definition. It is recommended that ≥ 4 attendances in a year be adopted as a consensus definition.